Innovations Dissemination Approaches among Government Co-Operative Supporting Organisations in Tanzania - Njau, Luka S; Mahonge, Christopher P; Massawe, Fatihiya A (International Journal of Sustainable Development & World Policy, 2020)
Efficient governments do encourage, support and promote innovations. Such realisation has necessitated some governments to establish strategic organisations to facilitate some of its innovation mandates. Some innovations have been developed by government co-operative supporting organisations (GCSOs) in Tanzania but only a few have been disseminated to end users. This has prompted questioning of the appropriateness of the innovations dissemination approaches used by such GCSOs. Research Method: The case study research design was used whereby five cases were picked. Primary data were collected using key informants’ (KIs) interviews, focus groups discussion (FGDs) and documentary review. A qualitative research approach was adopted. Data were analysed using content analysis. The Atlas.ti computer software facilitated analysis of the data. The results show that albeit the existence of several innovations dissemination approaches, there were no mechanisms to institutionalise the effective ones. Concurrently, the approaches applied largely left out the primary co-operative societies (PCSos) treating them as submissive receivers of innovations. Moreover, numerous setbacks including perceived unwillingness by GCSOs executives to prioritise and allocate available resources for innovations, inadequate incentives and resources deficit were constraining inclusive innovations dissemination efforts. The study covered GCSOs only as they have been receiving direct government resources to support among other things innovation activities unlike other member-based and private organisations operating in Tanzania.